COMPLICATIONS OF PERCUTANEOUS NEPHROSTOMY USING PIGTAIL NEPHROSTOMY TUBE SIZE OF 8 FRENCH VS PEDIATRIC NASOGASTRIC TUBE SIZE OF 8 FRENCH IN UROLITHIASIS PATIENTS IN HASAN SADIKIN HOSPITAL BANDUNG - Rizki, Dhika Ari; Tjahjodjati, Tjahjodjati (Indonesian Journal of Urology, 2018)
Objective: To compare the complications and patient-reported problems using standard pigtail nephrostomy tube versus pediatric nasogastric tube (NGT) usage as nephrostomy tube. Material & Methods: During 2015 period, 79 patients were referred to Urology Department in Hasan Sadikin Hospital Bandung for percutaneous nephrostomy procedure. Data were collected from Medical Record Urology Department to identify the complications and the patients-related problems using standard pigtail nephrostomy tube versus pediatric NGT usage as nephrostomy tube. Results: 38 patients (48%) using pigtail and 41 patients (52%) using pediatric NGT as nephrostomy tube. Overall,12 patients using pigtail nephrostomy tube (31.5%) experienced at least 1 complication related to nephrostomy procedure, and only 7 patients using pediatric NGT (17%) experienced complications. The complications including fever (3 patients), pyuria (5 patients), infection on insertion site (1 patient, 1.2%), pain (7 patients, 8.8%) hematuria (4 patients, 5%) and detached nephrostomy tube (19 patients, 24%). Conclusion: The small number of complications observed in pediatric nasogastric tube patient group suggest that pediatric NGT is a safe, cheap and widely available substitute for pigtail nephrostomy tube.